Optimization and anti-inflammatory evaluation of methyl gallate derivatives as a myeloid differentiation protein 2 inhibitor. Issue 20 (15th October 2019) - Qiu, Yinda; Xiao, Zhongxiang; Wang, Yanyan; Zhang, Dingfang; Zhang, Wenxin; Wang, Guangbao; Chen, Wenbin; Liang, Guang; Li, Xiaokun; Zhang, Yali; Liu, Zhiguo
Graphical abstract: Novel methyl gallate derivatives were synthesized, and evaluated their anti-inflammatory activities for the treatment of ALI as MD2 inhibitors. Highlights: Synthesized a series of novel methyl gallate derivatives (MGDs). Compound4k exhibited significant anti-inflammatory activity for treatment of ALI in vitro and in vitro . Compound4k was identified as a new MD2 inhibitor. Abstract: Myeloid differentiation protein 2 (MD2) is a co-receptor of toll-like receptor 4 (TLR4) responsible for the recognition of lipopolysaccharide (LPS) and mediates a series of TLR4-dependent inflammatory responses in inflammatory lung diseases including acute lung injury (ALI). Targeting MD2 thus may provide a therapeutic strategy against these lung diseases. In this study, we identified a novel compound4k with the potent anti-inflammatory activity among 39 methyl gallate derivatives (MGDs). MGD4k exhibited a high binding affinity to MD2, which in turn prevented the formation of the LPS/MD2/TLR4 complex. In addition, MGD4k significantly reversed the upregulation of LPS-induced inflammatory mediators such as tumor necrosis factor-α, interleukin-6, intracellular adhesion molecule-1, vascular cell adhesion molecule-1, and monocyte chemoattractant protein-1 in vitro and in vivo . Mechanistically, MGD4k performed anti-inflammatory function by inactivating JNK, ERK and p38 signaling pathways. Taken together, our study identified MGD4k as a novel potential therapeutic agent for ALI through inhibiting MD2, inflammatory responses, and major inflammation-associated signaling pathways.